Pancasila-Based Reconstruction Of Law And Human Rights In Local Governments’ Affairs And Agencies - Rachmad Safa’at; Harahab, Nuddin; Arrsa, Ria Casmi (Faculty of Law, University of Mataram, 2023)
As stated in Article 8 of Law (UU) Number 8 Year 1999 regarding Human Rights, the state’s government is obliged to protect and demonstrate its citizens’ Human Rights. The state shall be committed to establishing protection and implementation of Human Rights as a discourse of necessity between the State, Constitution, and Citizens. The correlation between these three is foregrounded in Article 28I Section 4 in the 1945 Constitution of the Republic of Indonesia. The law regarding the State’s obligation was later implemented by establishing the Ministry of Law and Human Rights and regional-level regulations by the Minister of Law and Human Rights Regulation Number 34 Year 2016 regarding the indicator standards of Human Rights in the Regency/Municipal levels. However, the regulation is presumably still inadequate at representing the Central Government and Local Government’s commitment to designing regulations integrating Human Rights in civil, political, socio-economic, cultural, and developmental rights. This study uses legal constructivism as its approach and aims to develop a legal system that implements principles of law and human rights in social institutions, legal institutions, social regulators, social integration, and social engineering. The results highlight the reconstruction of Law Number 23 Year 2014 regarding Local Government, which allows local government to administer Government affairs with the Minister's or Governor's joint approval. Furthermore, the Law a quo currently urges revisions in Article 12 regarding the concurrent government’s affairs on law and human rights. To achieve this, a nomenclature of provincial and regency/municipal Law and Human Rights Office (Diskumham) is on demand to handle affairs concerning law and human rights at regional levels, in accordance with Government Regulation Number 18 Year 2016 regarding Regional Agencies.